Cocoa Shell Extract Reduces Blood Pressure in Aged Hypertensive Rats via the Cardiovascular Upregulation of Endothelial Nitric Oxide Synthase and Nuclear Factor (Erythroid-Derived 2)-like 2 Protein Expression - Santiago Ruvira; Pilar Rodríguez-Rodríguez; David Ramiro-Cortijo; María Martín-Trueba; María A. Martín-Cabrejas; Silvia M. Arribas (MDPI AG, 2023)
Cocoa shell is a by-product of cocoa manufacturing. We obtained an aqueous extract (CSE) rich in polyphenols and methylxanthines with antioxidant and vasodilatory properties. We aimed to evaluate the effects of CSE supplementation in aged hypertensive rats on blood pressure and the mechanism implicated. Eighteen-month-old male and female rats exposed to undernutrition during the fetal period who developed hypertension, with a milder form in females, were used (MUN rats). Systolic blood pressure (SBP; tail-cuff plethysmography) and a blood sample were obtained before (basal) and after CSE supplementation (250 mg/kg; 2 weeks, 5 days/week). Plasma SOD, catalase activity, GSH, carbonyls, and lipid peroxidation were assessed (spectrophotometry). In hearts and aortas from supplemented and non-supplemented age-matched rats, we evaluated the protein expression of SOD-2, catalase, HO-1, UCP-2, total and phosphorylated Nrf2 and e-NOS (Western blot), and aorta media thickness (confocal microscopy). MUN males had higher SBP compared with females, which was reduced via CSE supplementation with a significant difference for group, sex, and interaction effect. After supplementation with plasma, GSH, but not catalase or SOD, was elevated in males and females. Compared with non-supplemented rats, CSE-supplemented males and females exhibited increased aorta e-NOS and Nrf2 protein expression and cardiac phosphorylated-Nrf2, without changes in SOD-2, catalase, HO-1, or UCP-2 in cardiovascular tissues or aorta remodeling. In conclusion, CSE supplementation induces antihypertensive actions related to the upregulation of e-NOS and Nrf2 expression and GSH elevation and a possible direct antioxidant effect of CSE bioactive components. Two weeks of supplementation may be insufficient to increase antioxidant enzyme expression.